A full three‐dimensional surface energy balance over a desert playa. (9th January 2023) - Morrison, Travis J.; Calaf, Marc; Pardyjak, Eric R.
Abstract: For decades, closure of the surface energy balance (SEB) has remained an outstanding problem for the atmospheric boundary layer (ABL) community. Despite many attempts at achieving closure following systematic approaches, universal closure remains elusive and only on rare occasions is it achieved. In this work, data from the unique spatial deployment of sensors from the Idealized Planar Array experiment for Quantifying Spatial heterogeneity (IPAQS 2019) field campaign are used to compute the three‐dimensional SEB. Results are compared with the traditional one‐dimensional SEB approach. The three‐dimensional SEB uses an integrated approach derived from the temperature tendency equation for a 400 m × $$ × $$ 400 m × $$ × $$ 2 m control volume over near‐canonical terrain, where the only complexities arise from time‐persistent surface thermal heterogeneities. Often neglected transport terms, such as advection and dispersive fluxes, are assessed and studied. Results show that, when using a three‐dimensional approach, it is possible to obtain an improved closure of the SEB during convective periods that can attain residual values of the order of accuracy of the instrumentation. Lastly, a theoretical development to account for the flux imbalance is presented that shows a promising approach for scaling the contribution of mean advective transport using onsite measurable variables. Abstract : For decades, closure of the surface energy balance (SEB) has remained an outstanding problem for the atmospheric boundary layer (ABL) community. In this work, data from the unique spatial deployment of sensors from the Idealized Planar Array experiment for Quantifying Spatial heterogeneity (IPAQS 2019) field campaign are used to compute the three‐dimensional SEB. Results show improved closure of the SEB, which can attain residual values of the order of accuracy of the instrumentation.